2021
DOI: 10.1080/21655979.2021.1939618
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating T-cell abundance combined with EMT-related gene expression as a prognostic factor of colon cancer

Abstract: EMT-related gene expression reportedly exhibits correlation with the anti-tumor immunity of T cells. In the present study, we explored the factors that might affect the efficacy of immunotherapy in colon cancer with treatment. In this regard, RNA-seq and clinical data of 469 colon cancer samples derived from the Cancer Genome Atlas (TCGA) database were used to calculate infiltrating T-cell abundance (ITA), to illustrate a pathway enrichment analysis, and to construct Cox proportional hazards (CPH) regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 63 publications
(77 reference statements)
1
1
0
Order By: Relevance
“…Previous studies showed that CXCL8 is involved in tumor angiogenesis and has been linked to promoting distant metastases in CRC(Karin 2018, Lukaszewicz-Zajac and Mroczko 2021). Our investigations revealed that CXCL-8 and TPM1, similar to classical tumor markers, predicted poor OS in patients with CRC, which is consistent with the results presented in other studies(Huang, Chen et al 2021, Luo, Tai et al 2022). KLF4 is a transcription factor that not only regulates physiological processes, such as cell proliferation, differentiation, and apoptosis, but also participates in the pathogenesis of in ammation and tumorigenesis(He, He et al 2023).…”
supporting
confidence: 93%
“…Previous studies showed that CXCL8 is involved in tumor angiogenesis and has been linked to promoting distant metastases in CRC(Karin 2018, Lukaszewicz-Zajac and Mroczko 2021). Our investigations revealed that CXCL-8 and TPM1, similar to classical tumor markers, predicted poor OS in patients with CRC, which is consistent with the results presented in other studies(Huang, Chen et al 2021, Luo, Tai et al 2022). KLF4 is a transcription factor that not only regulates physiological processes, such as cell proliferation, differentiation, and apoptosis, but also participates in the pathogenesis of in ammation and tumorigenesis(He, He et al 2023).…”
supporting
confidence: 93%
“…EMT-related proteins were regarded as risk factors for CRC in the previous studies. Huang et al found that an EMT-related gene expression signature combining infiltrating T-cell abundance has showed promising prognostic value in colon cancer [ 37 ]. Further, EMT-related gene expression signature can also be applied as a risk stratified tool in hepatocellular cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%